2017
DOI: 10.1038/onc.2017.359
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular matrix protein mindin attenuates colon cancer progression by blocking angiogenesis via Egr-1-mediated regulation

Abstract: Mindin, a secreted, highly conserved extracellular matrix (ECM) protein, exerts a broad spectrum of effects on the innate immune system. However, its function in colorectal cancer (CRC) progression is not well established, and its upstream regulation mechanisms remain unclear. Contrary to previous reports, this study used two different enzyme-linked immunosorbent assay (ELISA) kits to show that the serum level of mindin was significantly decreased in CRC patients and that this decreased level is more significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 55 publications
3
37
0
Order By: Relevance
“…A previous study shows that matrix metalloproteinase-9 is an important marker for analysis of the postoperative prognosis and risk of metastases in patients with colorectal cancer [ 35 ]. Recently, Wang et al showed that the extracellular matrix protein mindin attenuated colon cancer progression by blocking angiogenesis via Egr-1-mediated regulation [ 36 ]. Despite of extracellular matrix, the digestion function is closed related to cancer preventative activity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study shows that matrix metalloproteinase-9 is an important marker for analysis of the postoperative prognosis and risk of metastases in patients with colorectal cancer [ 35 ]. Recently, Wang et al showed that the extracellular matrix protein mindin attenuated colon cancer progression by blocking angiogenesis via Egr-1-mediated regulation [ 36 ]. Despite of extracellular matrix, the digestion function is closed related to cancer preventative activity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This early angiogenic switch emerges in premalignant or in in situ carcinomas. Neovasculature promotes solid tumor growth and metastasis . Therefore, targeting angiogenesis is one of the most conventional approaches for controlling tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Early growth response-1 (Egr-1), also called NGFI-A, is a zinc finger transcription factor and immediate early gene, which plays an important role in angiogenesis [ 14 , 15 ]. Meanwhile, Egr-1 may be involved in the pathogenesis of OA [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%